Experimental study of wood chip as partial replacement for coarse aggregate with ratio 5%, 10 and 15% - Mohamad Hafiz, Mohd Salehim (2017)
The purpose of this research is to determine the potential of utilization wood chip as partial replacement to coarse aggregate in concrete by experiment. The percent of replacement wood chip toward coarse aggregate by volume are 0%, 5%, 10% and 15%. The concrete mixes designed to reach 30MPa compressive strength at 28 days. The wood chip was soaked in water before mix them with concrete mix. Thus, wood chip will not absorb the water provided for hydration process and it help to improve bond at interface of wood chip and cement. Twenty four cube samples and twenty four prisms samples were mixed, casted and cured from eight trial mixes. The mixes are using 0.61 water to cement ratio. Four mixes with different percentages of replacement is for each sample ages. The water is used to cure the samples. The samples tested at 14 and 28 days ages. The laboratory tests conducted are slump, compressive strength and flexural strength. The tests are conducted according to ASTM standard test procedure. This research discovered that the mixes slump is not consistence as the percentage of replacement increase. This research also found that at age 14 and 28 days, 5% replacement sample produce higher compressive strength than 10% and 15%. At age 14 days, 5% replacement sample has highest flexural strength that surpasses the control concrete, while 10% replacement sample at 28 days age got the higher flexural strength than 5% and 15% but didn’t reach the control concrete flexural strength. For overall, control concrete sample still has highest compressive and flexural strength at 28 days. This research conclude that the utilization of wood chip is feasible and appropriate but need to be reminded that the strength of wood chip concrete is not as good as what it is design for.